Frequency of Breast Cancer in Women Under 40 Years at Ghulam Muhammad Mahar Medical College: A Cross-Sectional Study - Sadia Saher Memon; Shahid Hussain Mirani; Ghulam Fatima Komal Masood; Khalil Ahmed Channa; Halar Habibullah; Anam Rafique (Journal of the Dow University of Health Sciences)
Objective: To assess the frequency of breast cancer in women under the age of 40 and identify associated risk factors. Methods: A hospital-based cross-sectional study was carried out in the Department of Surgery at Ghulam Muhammad Mahar Medical College, Sukkur, Pakistan between August 2024 and January 2025. Women aged 15 to 39 years presenting with a palpable breast lump were included in the study. Breast cancer diagnosis was confirmed through histopathological examination, characterized by nuclear pleomorphism, tubular formation, and mitotic activity. Various risk factors, such as age, body mass index, marital status, smoking habits, family history of breast cancer, and duration of symptoms were recorded and analyzed to determine their association with breast cancer in this age group. Results: Among 199 women, the mean age was 37.50 ±2.34 years. Histopathological examination confirmed malignant lesions in 21 (10.5%) participants. The risk of malignancy was significantly higher among women who smoked (adjusted odds ratio [aOR] 8.04; 95% CI: 1.20–53.97; p-value 0.032) and those with a family history of breast cancer (aOR 11.84; 95% CI: 2.01–69.72; p-value 0.006). Conversely, women aged 36 years or younger had a markedly lower risk of malignancy compared to those over 36 years (aOR 0.04; 95% CI: 0.12–0.16; p-value < 0.001) Conclusion: A notable burden of breast cancer was found among women under 40, with a frequency of 10.5% in those presenting with palpable breast lumps. Smoking and a positive family history significantly increased the odds of malignancy.